Analisis Penerapan Metode Value Stream Mapping Pada Proses Bongkar Muat Kapal Container Untuk Meningkatkan Efisiensi Waktu Pada Pelabuhan Sunda Kelapa PT. Pelabuhan Indonesia (Pelindo) - Dwiki Faris Alamsyah; Amir Marasabessy (Fakultas Teknik UPN Veteran Jakarta, 2025)
The cargo container unloading and loading process is a critical component in port operations, significantly impacting logistical efficiency and operational costs. This study aims to analyze the application of Value Stream Mapping (VSM) to enhance time efficiency in loading and unloading activities at PT. Pelabuhan Indonesia (PELINDO). Inefficiencies in these processes often result in vessel departure delays, increased berthing times, and elevated operational expenditures. Using a quantitative approach, this research gathers primary data through direct field observations and interviews with key stakeholders at Tanjung Priok Port, supported by secondary data on vessel departure delays. The findings reveal multiple non-value-added activities and process waste contributing to inefficiencies. Based on VSM analysis, proposed improvements led to a significant reduction in process cycle time and enhanced overall port operational efficiency. The implementation of VSM proves to be an effective lean tool in streamlining container handling operations. These findings offer practical contributions to PT. Pelabuhan Indonesia in boosting performance and competitiveness, while also serving as a reference for future maritime logistics studies. Keywords: Value Stream Mapping; Time Efficiency; Loading and Unloading; Port Operations; Lean Manufacturing.